Políticas públicas e formação docente: um estudo dos Programas Gestar II e Progestão no município de Coronel João Sá - Carvalho, Jailda Evangelista do Nascimento (2013)
This work was developed in the Post - Graduate Education and fits within the Teacher Education Research: Knowledge and Skills, the Center for Postgraduate Education, Federal University of Sergipe - NPGED was a survey that was constituted from the need to investigate the public policy of teacher education in the city of Coronel João Sá Bahia, specifically through programs Learning Management School (Gestar II) and training Program for School Managers (Progestão). The question that guided the research was: what is the contribution of these programs for the training and practice of teachers working in the rural schools in the city of Coronel João Sá, Bahia? What is the meaning of this training for teaching practice from the rural context where they are inserted? The aim is to investigate the basis of the documents that support and practice place, the importance of these programs for training of teachers working in schools in the field in the city of Coronel João Sá-BA, in the years 2009 and 2010. This qualitative approach with studies from the reading of official documents and interviews. The analysis allowed us to infer that there is an urgent need for more specific public policies in the area of teacher training to ensure better working conditions and a field education that values and recognizes the ways of life in the field.